Tommaso e l'Islam - Gilioli, Giorgio (2020)
This article will deal with the relationship between Thomas Aquinas and the Islamic religion. An attempt was made to understand Aquinas' position through his works and to rediscover the seeds of a dialogue which, although difficult, proved to be intellectually honest and rigorous and which cannot be arbitrarily extrapolated from the historical-cultural context in which it matured.
Keywords: Christianity; Cristianesimo; Dio; Ebraismo; Ermeneutica; Essere; Faith; Fede; Fenomenologia; Filosofia; Filosofia della Religione; Glaube; God; Gott; Hebraism; Metafisica; Metaphysics; Monoteismo; Ontologia; Ontology; Phenomenology; Philosophy; philosophy of religion; Ragione; Reason; Religion; Religione; Religionsphilosophie